PERAN PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN KECERDASAN SPIRITUAL (Kajian Studi Literasi Pada Quran Surat Luqman Ayat 16, 17, 18 dan 19) - Andriyani, Wiwik Dyah; Salsabilah, Iis; Mubarok, H E. S; Saripudin, Saripudin; Nurdin, Dudung Ali (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2022)
In fact, every child is born intelligent, carrying their own potential and uniqueness which allows them to become intelligent. Howard Gardner in his book Multiple Intelligences, states that there are eight intelligences in humans, namely: linguistic/verbal/language intelligence, logical religious intelligence, visual/spatial/spatial intelligence, musical/rhythmic intelligence, physical kinesthetic intelligence, interpersonal intelligence, intrapersonal intelligence, and intelligence. naturalist. The task of parents and educators is to maintain the characteristics that form the basis of children's intelligence so that they survive until they grow up, by providing good environmental factors and stimulation to stimulate and optimize children's brain function and intelligence. Religious intelligence peaks in adolescence and early adulthood. Some high-level Religious abilities will decline after the age of 40. Logical religious intelligence is categorized as spiritual intelligence, because of its high support in the success of a person's studies. In the IQ test, logical religious intelligence is given priority. Therefore, religion becomes "meaningful" in the lives of individual humans.ABSTRAKSesungguhnya setiap anak dilahirkan cerdas dengan membawa potensi dan keunikan masing- masing yang memungkinkan mereka untuk menjadi cerdas. Howard Gardner dalam bukunya Multiple Intelligences, menyatakan terdapat delapan kecerdasan pada manusia yaitu: kecerdasan linguistik/verbal/bahasa, kecerdasan Agama logis, kecerdasan visual/ruang/spasial, kecerdasan musikal/ritmis, kecerdasan kinestetik jasmani, kecerdasan interpersonal, kecerdasan intrapersonal, dan kecerdasan naturalis. Tugas orangtua dan pendidik lah mempertahankan sifat-sifat yang menjadi dasar kecerdasan anak agar bertahan sampai tumbuh dewasa, dengan memberikan faktor lingkungan dan stimulasi yang baik untuk merangsang dan mengoptimalkan fungsi otak dan kecerdasan anak. Kecerdasan Agama memuncak pada masa remaja dan masa awal dewasa. Beberapa kemampuan Agama tingkat tinggi akan menurun setelah usia 40 tahun. Kecerdasan Agama logis dikategorikan sebagai kecerdasan spiritual, karena dukungannya yang tinggi dalam keberhasilan studi seseorang. Dalam tes IQ, kecerdasan Agama logis sangat diutamakan. Oleh karenanya, Agama menjadi “bermakna” dalam kehidupan individu manusia.